THE ROLE OF INSTITUTIONAL INVESTORS IN CORPORATE GOVERNANCE - Sobirjonov Samandar Murodil o’g’li,; Muslima Sadikova, (World Scientific Research Journal, 2025)
Abstract: Institutional investors now hold large equity stakes across developed and emerging markets, shifting from passive owners to active actors in corporate governance. This article examines how they shape outcomes through proxy voting, shareholder activism, board engagement, and exit strategies. Drawing on agency, stewardship, and stakeholder theories, it argues that institutional investors both curb managerial opportunism and support long-term value creation. Case evidence illustrates these dynamics in practice. For instance, CalPERS in the United States has shown that sustained shareholder activism can help to strengthen disclosure and boards. Similarly, Hermes Investment Management in the United Kingdom influenced reforms that later shaped the UK Stewardship Code. Recently, the Engine No. 1 campaign against ExxonMobil in 2021 demonstrated that even small activist funds can succeed when supported by large institutional investors such as BlackRock and Vanguard. Globally, Norway’s Global Pension Fund has promoted ethical investing by divesting from companies with low sustainability ratings, while the Tata-Mistry scandal in India highlights the growing role of institutional investors in emerging markets. Yet concerns persist about power concentration among the “Big Three,” conflicts of interest, and whether passive investing weakens oversight. Overall, institutional investors are key agents of reform, though effectiveness depends on context, incentives, and regulation.